Impact of 2020 Economic Recession on Advertising Agencies in Nigeria - Soji Alabi; Moshood-Abiola Arogundade (Britain International for Academic Research (BIAR-Publisher), 2025)
Existing literature tends to focus on broader marketing trends or global advertising shifts, leaving a gap in understanding how Nigerian agencies navigated the 2020 downturn and its implications for their future practices. This study seeks to address this gap by investigating the challenges faced by advertising agencies in Nigeria during the economic crisis. Qualitative research method was adopted, and data was gathered from ten (10) participants across five different advertising agencies in Nigeria. Additional findings revealed that the 2020 economic downturn had dual consequences for lead generation among advertising firms, depending on their ability to adapt to economic shifts and structural variations. While some formed international relationships and secured health awareness campaign gigs, others leveraged referrals to expand their business. Also, it was found that the 2020 economic recession exerted divergent effects on client-agency relationships within the advertising sector, contingent upon the agencies' responsiveness to the circumstances and their pre-existing operational frameworks. While some experienced cordial relationships through virtual collaborations, some relationships went sour. Based on the findings, it was recommended that advertising firms undertake digital transformation, incorporating remote collaboration tools and data-driven marketing techniques. Agencies can promptly capitalise on new opportunities, such as public health campaigns, by equipping their personnel with training in virtual client management and agile service delivery.